The Use Effects of Interactive Multimedia Edutainment on The Achievement Improvements in Mathematics - Ade Saepudin; Saluky Saluky; Muhammad Ali Misri (ITEJ (Information Technology Engineering Journals), 2016)
The aim of this study was 1) to determine the students 'response to the use of interactive multimedia-based edutainment 2) the improvement of students' mathematics achievement 3) to determine the effect of the use-based interactive multimedia edutainment to increase student mathematics achievement. This research is a quantitative method used was experimental research design pretest posttest control group. The population in this study were students of class VII MTs.KHAS Kempek Cirebon 2015-2016 school year. Sample class VII E as the control class VII and class C as the experimental class. Data collection techniques in this study a questionnaire and tests. Based on the results of data processing, showed that students responded very well to the use of interactive multimedia-based edutainment. This is evidenced by the average percentage of each indicator by 84%. Mathematics achievement test results of students in the experimental class to change the value of an average of 48,75 while in the control group experienced changes in the average value of 34,04. Based on the results of regression testing using SPSS 21.00 correlation coefficient (r) = 0,777 which is included in the category of strong and coefficient of determination () = 0,603, or 603%. The regression equation is Y = -114,714 + 1,561X. This equation has a coefficient of linear regression direction (b) = 1,561 is positive, meaning that the response of students moved up one unit, then the student achievement in mathematics will increase 1,561 times. Statistical analysis showed that tcount> table = 8,273> 1,68. This means there is significant influence based interactive multimedia edutainment use to increase student mathematics achievement. The magnitude of effect was 60,3% and the rest influenced by other factors. Key Words: Based Interactive Multimedia Edutainment, Learning Achievement